Secondary sedimentary structures associated with fluidization zones in Permo-Carboniferous redbeds of Prince Edward Island, Canada - van de Poll, H.; Plint, A. (Atlantic Geology)

(untitled) (Maritime Sediments Editorial Board, 1983)
Internal parting surfaces associated with fluidization tones up to 20b in length, occurring In the alluvial redbeds of Prince Edward Island contain secondary sedimentary structures resembling sole marks. These are described and their origin considered in terms of physical diagenesis. Rapidly escaping pore water in conjunction with load deformation within fluidized zones during dewatering and compaction of the redbeds are thought to have been the principal processes involved in the formation of these structures.